Aplikasi Pupuk Hayati Pelarut Fosfat dalam Upaya Peningkatan Pertumbuhan dan Produksi Beberapa Varietas Tanaman Kedelai (Glycine max L.) - Girsang, Rosmaria; Br Sitepu, Sri Mahareni; Kurniawan, Rizki (UNIVERSITAS LABUHANBATU, 2024)
Soybean is a plant that has a significant role in responding to food needs and improving people's nutrition because it is an economically affordable source of vegetable protein when compared to other protein sources such as meat, milk and fish. The use of superior seed varieties and supported by the use of appropriate fertilizer also has a very important role in the continued growth of soybean plants. This research used a Randomized Block Design (RAK) with 2 factors and 3 replications to obtain 36 research plots. Factor I Biological Fertilizer (H) which consists of 4 levels, namely: H0 = 0 ml/liter.air/plant, H1=10 ml/ liter.air /polybag, H2=20 ml/ liter.air/polybag, H3= 30 ml/ liter. water/polybag. Factor II Soybean Variety (V) which consists of 3 levels, namely: V1 = Dega 1 Variety, V2 = Ring 1 Variety, V3 = Devon 1 Variety. The results showed that the use of biological fertilizer had no significant effect on all observed parameters, whereas The use of varieties has a very significant effect on all observed parameters. Keywords: soybean, fertilizer, varieties